The nanoprodrug of polytemozolomide combines with MGMT siRNA to enhance the effect of temozolomide in glioma. (31st December 2023) - Xu, Haoyue; Zhang, Yongkang; Li, Linfeng; Ren, Yanhong; Qian, Feng; Wang, Lansheng; Ma, Hongwei; Quan, Ankang; Liu, Hongmei; Yu, Rutong
Abstract: Temozolomide (TMZ) is a conventional chemotherapeutic drug for glioma, however, its clinical application and efficacy is severely restricted by its drug resistance properties. O6-methylguanine-DNA methyltransferase (MGMT) is a DNA repair enzyme, which can repair the DNA damage caused by TMZ. A large number of clinical data show that reducing the expression of MGMT can enhance the chemotherapeutic efficacy of TMZ. Therefore, in order to improve the resistance of glioma to TMZ, an angiopep-2 (A2) modified nanoprodrug of polytemozolomide (P(TMZ)n) that combines with MGMT siRNA (siMGMT) targeting MGMT was developed (A2/T/D/siMGMT). It not only increased the amount of TMZ within tumor lesion site, but also reduced MGMT expression in glioma. The in vitro experiments indicated that the A2/T/D/siMGMT effectively enhanced the cellular uptake of TMZ and siMGMT, and resulted in a significant cell apoptosis and cytotoxicity in the glioma cells. The in vivo experiments showed that glioma growth was inhibited and the survival time of animals were prolonged remarkably after A2/T/D/siMGMT was injected via tail vein. The results showed that the therapeutic effect of A2/T/D/siMGMT in the treatment of glioma was significantly improved.